Visible‐Light‐Induced Selective Defluoroborylation of Polyfluoroarenes, gem‐Difluoroalkenes, and Trifluoromethylalkenes. (23rd January 2020) - Xu, Wengang; Jiang, Heming; Leng, Jing; Ong, Han‐Wee; Wu, Jie
Abstract: Fluorinated organoboranes serve as versatile synthetic precursors for the preparation of value‐added fluorinated organic compounds. Recent progress has been mainly focused on the transition‐metal catalyzed defluoroborylation. Herein, we report a photocatalytic defluoroborylation platform through direct B−H activation of N‐heterocyclic carbene boranes, through the synergistic merger of a photoredox catalyst and a hydrogen atom transfer catalyst. This atom‐economic and operationally simple protocol has enabled defluoroborylation of an extremely broad scope of multifluorinated substrates including polyfluoroarenes, gem ‐difluoroalkenes, and trifluoromethylalkenes in a highly selective fashion. Intriguingly, the defluoroborylation protocol can be transition‐metal free, and the regioselectivity obtained is complementary to the reported transition‐metal‐catalysis in many cases. Abstract : Die selektive Defluorborylierung von Polyfluorarenen, gem ‐Difluoralkenen und Trifluormethylalkenen gelingt durch Photoredox‐ und Wasserstoffatomtransfer‐induzierte B‐H‐Aktivierung. Die Reaktionen liefern fluorierte Organoborane als Bausteine für höherwertige Organofluorverbindungen.